The Effect of Android-based Pregnancy Education and Care on Improving The Behavior of Pregnant Women - Indah Sari Setyaningrum; Tatarini Ika Pipitcahyani; Evi Pratami; Ani Media Harumi; Zarinah Binti Abdul Aziz (International Journal of Advanced Health Science and Technology, 2023)
Pregnancy begins with the meeting of egg and sperm cells so that fertilization occurs, followed by implantation until the birth of the fetus. The coronavirus pandemic has led to various limitations, shortages of personal protective equipment (PPE), fear of being overwhelmed with COVID-19 cases. The maternal mortality rate increased in 2021 during the Covid-19 pandemic to reach 234.7 per 100,000 live births. The lowest MMR was in Surabaya, which was 42.33 per 100,000 live births. This study used a quantitative approach with a Quasi-Experimental design using a One-group pretest-posttest design with a sample of 51 respondents and 1 intervention group. The technique for taking samples using Purposive Sampling. The research instrument used a questionnaire sheet to determine the behavior of pregnant women. This research was conducted in February - April 2023. The analytical method used univariate and bivariate analysis using the Wilcoxon test. The results showed that there was a significant increase in behavior with the result that the p value on knowledge = 0.005 p < α (0.05), attitude = 0.008 p < α (0.05), action = 0.019 p < α (0.05). The results of the study showed the effect of using Android-based educational and treatment applications to increase behavior in pregnant women. So it is advisable for pregnant women to use Android-based pregnancy education and care applications to increase knowledge, attitudes, and actions about pregnancy.